Assessment of the Effectiveness of Ultrasound-Guided Needle Aspiration of Lactating Breast Abscesses - Tran AT; Nguyen DM; Tran QH; Nguyen QH; Nguyen Thi TH; Tran Thi DQ; Luu HN; Do Thi YM (International Journal of General Medicine, 2024)
Anh Tuan Tran,1– 3,* Dinh Minh Nguyen,4,* Quang Hien Tran,5,6 Quang Hung Nguyen,7 Thu Ha Nguyen Thi,1 Do Quyen Tran Thi,1 Hong Nhung Luu,1 Yen Mai Do Thi1 1Radiology Center, Bach Mai Hospital, Hanoi, Vietnam; 2Radiology Department, University of Medicine and Pharmacy, Hanoi National University, Hanoi, Vietnam; 3Stroke and Brain Vascular Disease Department, University of Medicine and Pharmacy, Hanoi National University, Hanoi, Vietnam; 4Radiology Department, Viet Duc Hospital, Hanoi, Vietnam; 5An Giang Department of Health, An Giang, Vietnam; 6Obstetrics and Gynecology, an Giang Women’s and Children’s Hospital, An Giang, Vietnam; 7Oncology and Nuclear Medicine Center, Bach Mai Hospital, Hanoi, Vietnam*These authors contributed equally to this workCorrespondence: Quang Hien Tran, An Giang Department of Health, Obstetrics and Gynecology, an Giang Women’s and Children’s hospital, 15 Le Trieu Kiet Street, Long Xuyen City, An Giang, Vietnam, Tel +84913104293, Email tranquanghienag@yahoo.comObjective: To evaluate the effectiveness of ultrasound-guided needle aspiration in treating lactating breast abscesses.Methods: This study was conducted in Bach Mai Hospital, from 6/2020 to 7/2021. Lactating patients with breast abscesses underwent ultrasound-guided aspiration followed by antibiotics therapy.Results: There were 59 lactating patients with 82 breast abscesses. Most of the abscesses had heterogeneous echogenicity, no capsule, and a size smaller than 5cm. Bacterial culture results showed that 85.4% of cases were Methicillin-resistant Staphylococcus aureus. The number of aspirations was from 1 to 5. The cure rate was 91.5%, and 5.3% of these cases had a complication associated with galactocele after treatment.Conclusion: Ultrasound-guided needle aspiration is a minimally invasive treatment option for lactating breast abscesses with a high complete cure rate and good cosmetic results.Keywords: breast abscess, ultrasound-guided needle aspiration